Cytogenetics of Cheniella (Leguminosae: Cercidoideae) from China and Vietnam - Shi-Ran Gu; Hong-Yan Li; Xiang-Xu Huang; Hong Yang; Xia Peng; Zhu-Qiu Song; Lei Duan; Miao-Miao Shi; Xiang-Ping Wang; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu; et al. (Caryologia)
The cytogenetics of Cheniella, a recently segregated genus of the early-diverging subfamily Cercidoideae of Leguminosae, remain understudied, hindering our understanding of the cytological evolution and the utilization of this important plant group. Here we conducted comparative cytogenetic studies on 11 species and one subspecies of Cheniella and one species of its sister genus Phanera. Unlike earlier reports which recovered 2n=28 for two Cheniella species, we consistently observed chromosome counts of 2n=26 for all 11 species of Cheniella, supporting the segregation of Cheniella from Phanera, which consistently exhibited 2n=28 in this and previous studies. Our analyses, along with previous cytogenetic data, indicates that 2n=14, 2n=26 and 2n=28 are the predominant chromosome numbers in the basal-most genus Cercis, Cheniella and the remainder genera, respectively. The ancestor of the subfamily is most probably a diploid with 2n=14, with subsequent polyploidization followed by chromosome reduction events leading to 2n=28 and 2n=26 in the other lineages. Our results provide new insight into the cytotaxonomy and chromosome evolution of Cercidoideae, also lay the foundation for future genomics research.